POTENSI FOTODINAMIK SEBAGAI MODALITAS TERAPI ALTERNATIF NON INVASIF PADA ORAL CANCER - Timotius William Yusuf; Jason Chen; Vincentius Mario Yusuf (Kelompok Ilmiah Hippocrates Fakultas Kedokteran Universitas Udayana, 2022)
Introduction: Oral cancer is defined as a type of malignancy that occurs in the oral cavity and occupies the top 10 leading causes of cancer worldwide. Oral cancer mortality rate is high with a five-year survival rate of only 50-60%. The current treatment is invasive, risky, with severe complications that can reduce therapy efficacy and patients’ quality of life. Based on previous studies, photodynamics is a promising alternative therapy for oral cancer because of its selective non-invasive traits and good clinical results. Methods: This literature review was done based on PICO and determined inclusion criterias. Studies were extracted from “PubMed”, “ScienceDirect”, and “SpringerLink” databases using “boolean operator” search method. Results & Discussion: There were a total of 11 clinical studies that met the inclusion criteria and stated that photodynamic therapy was effective in the treatment of oral cancer. Clinical efficacy is seen from high complete response rates and survival rates accompanied by low recurrence rates. The mechanism underlying its efficacy is photosensitizer excitation triggers the production of reactive oxygen species that lead to the destruction of cancer cells. It was also found that photodynamic exposure can cause shut-down of tumor tissue blood vessels and activation of immune system. The most common side effects are pain, swelling, and photosensitivity. In general, side effects found are not fatal, can be controlled and do not cause lasting functional or aesthetic impacts. Conclusion: Photodynamic is effective as a non-invasive therapy modality in oral cancer with good clinical efficacy and safety profile.